2006
DOI: 10.1007/s11726-005-0300-2
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the efficacy of mind-calming and brain-refreshing acupuncture and moxibustion for treating 42 anxiety patients

Abstract: 摘要 目的:观察针刺配合艾灸治疗焦虑症的疗效。方法:以针刺配合艾灸治疗焦虑 症 42 例为治疗组,同时随机设西药治疗 45 例为对照组,进行对照观察。结果:治疗 组总有效率 92.9%,对照组 71.1%,两组差异有显著性意义(P<0.01)。结论:治疗组明 显优于对照组,且无副作用和药物依赖性。 关键词 焦虑症; 针灸疗法; 药物疗法 Abstract Objective: To investigate the efficacy of acupuncture in cooperation with moxibustion for treating anxiety. Methods: A treatment group of 42 anxiety patients was treated by acupuncture in cooperation with moxibustion and a control group of 45 anxiety patients, with Western medicine. Results: The total efficacy rate was 92.9% in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A total of 459 articles related to Chinese and English were retrieved by computer and manual retrieval, including 168 articles on CNKI, 158 articles on Wanfang data, 70 articles on VIP and 63 articles on Pubmed. After reading the title, abstract and full text of the research literature, screening according to the research purpose, inclusion criteria and exclusion criteria, 19 RCT literatures were finally decided to be included [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The specific retrieval process is shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 459 articles related to Chinese and English were retrieved by computer and manual retrieval, including 168 articles on CNKI, 158 articles on Wanfang data, 70 articles on VIP and 63 articles on Pubmed. After reading the title, abstract and full text of the research literature, screening according to the research purpose, inclusion criteria and exclusion criteria, 19 RCT literatures were finally decided to be included [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The specific retrieval process is shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…After evaluating the methodological quality of the 19 references [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] included, it was found that there is a high quality [14] and the rest were of low quality. All the literatures are RCTS and mention the use of random methods for grouping, but the random methods are not described in detail.…”
Section: Quality Evaluation Of Included Literature Methodologymentioning
confidence: 99%
See 1 more Smart Citation